Nontraumatic shoulder pain affects proprioception and dynamic stability in female high school volleyball players - Mizoguchi, Y.; Suzuki, K.; Hasegawa, S.; Shimada, N.; Kimura, F.; Hall, T.; Akasaka, K. (Journal of Athletic Training, 2025)
Context Nontraumatic shoulder pain (NSP) is common in volleyball, affecting performance and well-being. It is more prevalent in female players. Previous studies lack comprehensive assessments of shoulder pain that consider multiple factors, including range of motion, muscle strength, joint position sense, dynamic stability, and volleyball-specific mechanics.